EFFECTIVENESS OF ROLE-PLAYING METHOD TOWARDS STUDENT’S PARTICIPATION IN SOCIAL STUDIES LEARNING AT ELEMENTARY SCHOOL - Maria Dewi, Sinta; Wulan Anggraeni, Sri; Tresnawati, Rina (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the differences in the effectiveness of student learning participation in social studies subjects using the role-playing method and those who do not use the role-playing method in fifth grade students at Margasari II Elementary School in 2018/2019 Academic Year. This research is quantitative research with quasi experimental research type. Test instrument used to determine student participation in social studies learning by using a questionnaire test. The results of data analysis in the experimental class pretest the value obtained is still low value obtained by 16.00, while the control class is 18.00. After treatment is carried out learning using the role-playing method. The results of the analysis in the experimental class posttest showed that participation in social studies learning students increased by an average of 19.00, while in the control class an average value of 17.00 was obtained. Based on the t test conducted sig (2-tailed) <0.05 which means that there are differences in student participation in social studies learning. From the results of the research that has been done, it can be concluded that there are differences in the effectiveness of the role-playing method on the participation of students in social studies learning in 5th grade at Margasari II Elementary School in 2018/2019.